Sunny-side up [braille] - Giff, Patricia Reilly (Giff, Patricia Reilly. Kids of the Polk Street School, 1986)
Summer for Richard Best, nicknamed Beast, means facing the two ordeals of summer school and losing his best friend, who is moving to a distant state.